2021
DOI: 10.1002/ece3.7592
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated vegetation succession but no hydrological change in a boreal fen during 20 years of recent climate change

Abstract: Northern mires (fens and bogs) have significant climate feedbacks and contribute to biodiversity, providing habitats to specialized biota. Many studies have found drying and degradation of bogs in response to climate change, while northern fens have received less attention. Rich fens are particularly important to biodiversity, but subject to global climate change, fen ecosystems may change via direct response of vegetation or indirectly by hydrological changes. With repeated sampling over the past 20 years, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 134 publications
4
18
0
Order By: Relevance
“…This result is in line with the idea that microtopography controls the moisture regime and methanotroph/methanogen communities of Sphagnum and thus methane oxidation in northern peatlands (Basiliko et al., 2004). The importance of vegetation and topographic controls on CH 4 exchange emphasizes that, while WT may govern CH 4 fluxes in the short term, ecosystem succession in response to drying, including vegetation change and alteration of hummock‐hollow topography (Kolari et al., 2021; Robitaille et al., 2021) could have more significant effects on long‐term CH 4 exchange and spectral indices of wetness alone would not be sufficient to evaluate changes in CH 4 exchange over longer time periods.…”
Section: Discussionmentioning
confidence: 99%
“…This result is in line with the idea that microtopography controls the moisture regime and methanotroph/methanogen communities of Sphagnum and thus methane oxidation in northern peatlands (Basiliko et al., 2004). The importance of vegetation and topographic controls on CH 4 exchange emphasizes that, while WT may govern CH 4 fluxes in the short term, ecosystem succession in response to drying, including vegetation change and alteration of hummock‐hollow topography (Kolari et al., 2021; Robitaille et al., 2021) could have more significant effects on long‐term CH 4 exchange and spectral indices of wetness alone would not be sufficient to evaluate changes in CH 4 exchange over longer time periods.…”
Section: Discussionmentioning
confidence: 99%
“…The interaction between climate and pH niches explains niche shifts reported by previous comparisons between Scandinavia and Western or Central Europe (Graham et al, 2019; Kooijman & Westhoff, 1995; Peterka et al, 2020), or between cold mountains of the Balkans and warmer Central‐European fens (Hájková et al, 2008). The same explanation may apply to observations that the occurrences of some fen mosses had become more limited to the most base‐rich fens during recent decades across Europe (Hájek et al, 2015; Kolari et al, 2021).…”
Section: Discussionmentioning
confidence: 82%
“…Niche extension of acidophytic and calcium‐tolerant species towards high‐pH habitats is facilitated when nutrient, especially potassium, availability is improved or if the level of alkaline groundwater decreases in warmer climates. Previous studies across Europe (Kooijman, 2012; Kooijman & Bakker, 1995; Hájek et al, 2015; Kolari et al, 2021; Plesková et al, 2016; Vicherová et al, 2017) have indeed demonstrated expansion of Sphagnum teres , S . squarrosum , S .…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations